Us - Pescod, Hannah; Lees, Pat; Sax, Geoffrey; Hollander, Tom, 1967-; Reeves, Saskia; Taylor, Tom, 2001-; Bramhill, Gina; Nicholls, David, 1966-; PBS Distribution (Firm) (Arlington, VA : PBS, 2021)
Three weeks, six countries and one divorce? What was supposed to be the holiday of a lifetime becomes a desperate quest for Douglas Petersen to save his marriage. From the bestselling novel by David Nicholls.
Title from disc surface.
Based on the bestselling book by David Nicholls.
Special features: from book to screen; the world of us; a holiday romance.
Based on the book by David Nicholls.
Tom Hollander, Saskia Reeves, Tom Taylor, Gina Bramhill, Iain de Caestecker.
Rating: TV-14.
Keywords: Nicholls, David, -- 1966- -- Television adaptations; Middle age -- Drama; Married people -- Drama; Man-woman relationships -- Drama; Television mini-series.; Television adaptations; Television programs